PENGARUH METODE PERMAINAN PUZZLE TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK - widiagustiningsih, Kadek (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE One abilities aspect that should be developed of kindergarten children is reading . Reading is the basis for mastering a variety of fields of study. This type of education is given in kindergarten emphasizes the essence of play for children. Therefore, the method puzzle game is one kind of games that can be used. By playing puzzle will unwittingly trained his brain to concentrate. It is expected by the method of puzzle games will help improve beginning reading skills in children. This study aims to determine the effect of the method puzzle game toward the begining reading skills of kindergarten children B1 class of Kemala Bhayangkari 4 Gianyar . This research is a study of pre experiments with the approach one group pre-post test design. The sample consisted of 30 children class B1 obtained with a total sampling. All respondents are given methods intervenstion of puzzle game in 12 sessions with duration of 15 minutes. The beginning ability of read ing was observed by the word count in pre-test and post-test those were able to read by respondent of 10 words that have been prepared. The results were obtained 3 respondents (10%) were able to read 3 words, 6 respondents (20%) were able to read 4 words, 18 respondents (60%) were able to read 5 words, and a third of respondents (10%) were able to read 6 words before applied methods puzzle game. Once applied the method puzzle game, most of the respondents have been able to read 10 words given by 24 respondents (80%), 3 respondents (10%) were able to read 7 words, and 3 respondents (10%) were able to read 8 words. Based on the nonparametric Wilcoxon test, this difference was statistically significant, with p value = 0.000, which means there is a puzzle game method to influence the beginning reading skills in kindergarten children B1class of Kemala Bhayangkari 4 Gianyar /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: puzzle, beginning reading skills